Դարձվածային փոխառությունները և օտարաբանությունը ժամանակակից հայերենում - Ա. Ա. Մկրտումյան (ՀՀ ԳԱԱ հրատ.)
Фразеологические заимствования и варваризмы являются единицами функциональных стилей языка. Фразеологические варваризмы–это лексические единицы, вошедшие в армянскую лексику из других языков, но имеющие армянские эквиваленты. Их употребление нежелательно и может быть продиктовано лишь стилистическими задачами. Phraseological barbarisms and loanwords are the units of functional style of the language. Phraseological barbarisms are lexical units which have been shifted into the wordstock of the Armenian language from foreign languages. They have their equivalents, too. Their usage is not desirable and is used only for practical cases.
Keywords: Philology; Linguistics; Language and Literature